Mapping of the Security Requirements of GDPR and NISD - Najmudin Saqib; Vasileios Germanos; Wen Zeng; Leandros Maglaras (EAI Endorsed Transactions on Security and Safety, 2021)
Privacy and information security have consistently been a priority for the European Union lawmaker. This paper investigates the security requirements of the General Data Protection Regulation (GDPR) and the Directive on security of network and information systems (NISD). This investigation incorporates what is unique about the NISD; how it overlaps with existing frameworks; and how security requirements in the GDPR influence the NISD. This mapping of requirements can help businesses and organizations to distinguish possible difficulties that may experience while conforming to GDPR and NISD, and help them create a consistent cybersecurity framework and structure new security plans.